The alkenylacyl class of ethanolamine phospholipid represents a major form of eicosapentaenoic acid (EPA)-containing phospholipid in the platelets of human subjects consuming a fish oil concentrate - Holub, B.J; Celi, B; Skeaff, C.M (Thrombosis research, 1988)
A quantitative assessment was made of the distribution of arachidonic acid (AA), eicosapentaenoic acid (EPA), docosapentaenoic acid (DPA), and docosahexaenoic acid (DHA) among the individual sub-classes (diacyl, alkylacyl, alkenylacyl) of the various platelet phospholipids of human subjects consuming a fish oil concentrate (as MaxEPA) enriched in EPA plus DHA. This work was of interest since dietary fish oils provide for a pronounced enrichment of platelet phospholipid in EPA as well as DPA plus DHA to a lesser extent while reducing AA-phospholipid and platelet reactivity. After 42 days of MaxEPA supplementation (providing 3.6 g EPA and 2.4 g DHA per day), the majority of the mass of all four polyunsaturated fatty acids in the choline-containing phospholipid (PC) was found in the diacyl species (76–87% of total PC). In contrast, twice as much of the EPA in the ethanolamine-containing phospholipid (PE) resided in the alkenylacyl species (62.7% of total PE) relative to the diacyl species (32.3%) with minor amounts in the alkylacyl fraction (5.1%). The major single reservoir of total EPA-containing phospholipid was the alkenylacyl PE (38.2% of total) followed by diacyl PC (27.8%), diacyl PE (19.6%), with progressively lesser amounts in the alkylacyl PC, alkylacyl PE, diacyl PS (phosphatidylserine), alkenylacyl PC, and diacyl PI (phosphatidylinositol) at 6.7, 3.1, 2.3, 1.4, and 0.8% of the total mass, respectively. In contrast, only 27.1% of the total mass of AA-phospholipid was represented by the alkenylacyl PE with the bulk of the remainder being distributed in the diacyl species of PE, PC, PI, and PS. The single major reservoir for DPA was alkenylacyl PE (41.8% of total DPA-phospholipid) whereas DHA was equally distributed between alkenylacyl and diacyl PE (28.1 and 27.5%, respectively). The accumulation of EPA in alkenylacyl PE of human platelets upon the consumption of fish oil containing n-3 polyunsaturated fatty acids may be of importance in relation to the diminution in platelet reactivity and thromboxane A 2(TXA 2) synthesis as well as the production of 3-series prostaglandins including TxA 3.